A phenological study of coalescence in two South African Gigartinales, Gigartina polycarpa (Kützing) Setchell et Gardner and Sarcothalia stiriata (Turner) Leister - Wolf, Gabrielle (Department of Biological Sciences, 2017)
Coalescence has been described in a number of coalescing red algae, however the majority of studies are laboratory based. This study examines the phenology of clumping characteristics in Gigartina polycarpa and Sarcothalia stiriata in the field. Clumps of these two species appear to have a coalesced holdfast from which a number of uprights arise. Clumps of both species display characteristics previously described in coalescing species. This includes size inequality between fertile uprights and juvenile and non-fertile uprights and a loose relationship between basal area and number of uprights. It appears that the phenology of clumps supports previous studies examining phenology without considering coalescence. The distribution of the two species is very different, with a higher proportion of S. stiriata conspecifics found next to each other. Conversely G. polycarpa has a low proportion of near neighbour conspecifics.